Does Government R&D Policy Mainly Benefit Scientists and Engineers? - Goolsbee, Austan (American Economic Review, 1998)
Conventional wisdom holds that the social rate of return to R&D significantly exceeds the private rate of return and, therefore, R&D should be subsidized. In the U.S., the government has directly funded a large fraction of total R&D spending. This paper shows that there is a serious problem with such government efforts to increase inventive activity. The majority of R&D spending is actually just salary payments for R&D workers. Their labor supply, however, is quite inelastic so when the government funds R&D, a significant fraction of the increased spending goes directly into higher wages. Using CPS data on wages of scientific personnel, this paper shows that government R&D spending raises wages significantly, particularly for scientists related to defense such as physicists and aeronautical engineers. Because of the higher wages, conventional estimates of the effectiveness of R&D policy may be 30 to 50% too high. The results also imply that by altering the wages of scientists and engineers even for firms not receiving federal support, government funding directly crowds out private inventive activity.